Echoes of Absence: Exploring the Lived Experiences of Psychology Students without Paternal Presence - Nicole Balba; Airiz Mae Banila; Arnold Janssen Belleza; Elisha Hezekiah Blanqueza; Zhecainnah Rhay Bondad; Princess Julie Ann Garcia (RSF Press, 2026)
This qualitative research investigates the lived experiences of Psychology students who grew up without paternal presence, with emphasis on emotional development, attachment patterns, and identity formation. Interpretive Phenomenological Analysis (IPA), an advanced qualitative approach, was carefully employed to capture the depth and complexity of participants’ meaning-making. Seven students aged 18–21 were selected through homogeneous purposive sampling, and semi-structured interviews revealed five (5) emergent themes: (1) Strength, reflecting resilience, self-reliance, and responsibility; (2) Relational Dynamics, highlighting interactions with family and peers; (3) Inner Disconnection, capturing emotional detachment and difficulty expressing vulnerability; (4) Adaptive Coping, describing strategies for navigating challenges of father absence; and (5) Emotional Complexities, encompassing conflicting emotions arising from paternal loss. Grounded in Bowlby’s Attachment Theory, the study demonstrates how paternal absence influences emotional regulation, relational dynamics, and self-concept. Participants reported premature independence, emotional suppression, and relational distance, yet also demonstrated resilience and personal growth. Many used their experiences as motivation to pursue psychology, aiming to support others with similar backgrounds. This study contributes to qualitative psychology by deepening the understanding of attachment disruptions and identity development in emerging adulthood. It extends phenomenological research on father absence by highlighting how psychology students’ reflective capacities shape distinct interpretations of paternal loss. While paternal absence presents risks such as emotional instability and identity confusion, it can also foster adaptive coping, heightened self-awareness, and a drive for transformation. These insights offer implications for counseling support, psychology education, and future qualitative inquiry, particularly in contexts where paternal absence is a widespread social and cultural reality